Quaking Deficiency Amplifies Inflammation in Experimental Endotoxemia via the Aryl Hydrocarbon Receptor/Signal Transducer and Activator of Transcription 1–NF-κB Pathway - Wang, Li; Zhai, Dong-Sheng; Ruan, Ban-Jun; Xu, Cheng-Ming; Ye, Zi-Chen; Lu, Huan-Yu; Jiang, Ying-Hao; Wang, Zhen-Yu; Xiang, An; Yang, Yuan; Yuan, Jian-Lin; Lu, Zi-Fan (Frontiers in Immunology, 2017)
Macrophages, characterized by considerable diversity and plasticity, play a crucial role in a broad spectrum of biological processes, including inflammation. However, the molecular mechanisms underlying the diverse phenotypes of macrophages are not well defined. Here we show that the RNA-binding protein, quaking (QKI), dynamically modulates macrophage polarization states. After lipopolysaccharide (LPS) stimulation, QKI-silenced RAW 264.7 cells displayed a pro-inflammatory M1 phenotype characterized by increased expression of iNOS, TNF-α, and IL-6 and decreased expression of anti-inflammatory factors, such as IL-10, found in inflammatory zone (Fizz1), and chitinase-like 3 (Chil3 or Ym1). In contrast, QKI5 overexpression led to a suppressive phenotype resembling M2 macrophages, even under M1 differentiation conditions. Moreover, myeloid-specific QKI-deficient mice tended to be more susceptible to LPS-induced endotoxic shock, while the exogenous transfer of macrophages overexpressing QKI5 exerted a significant improving effect. This improvement corresponded to a higher proportion of M2 macrophages, in line with elevated levels of IL-10, and a decrease in levels of pro-inflammatory mediators, such as IL-6, TNF-α, and IL-1β. Further mechanistic studies disclosed that QKI was a potent inhibitor of the nuclear factor-kappa B (NF-κB) pathway, suppressing p65 expression and phosphorylation. Strikingly, reduced expression of the aryl hydrocarbon receptor (Ahr) and reduced phosphorylation of signal transducer and activator of transcription 1 (STAT1) in QKI-deficient cells failed to restrain the transcriptional activity of NF-κB and NRL pyrin domain containing 3 (NLRP3) activation, while restoring QKI expression skewed the above M1-like response towards an anti-inflammatory M2 state. Taken together, these findings suggest a role for QKI in restraining overt innate immune responses by regulating the Ahr/STAT1-NF-κB pathway.